Tissue distribution and anti-inflammatory activity of corticosteroids incorporated in lipid emulsion. Issue 3 (June 1982) - Mizushima, Y; Hamano, T; Yokoyama, K
Abstract : Dexamethasone palmitate was incorporated into a lipid emulsion (Intralipid, Intralipos) and was injected into rats, and its distribution in the organs and tissues and its anti-inflammatory effects were compared with those of free dexamethasone disodium phosphate. The distribution patterns of [3H] dexamethasone were markedly different between the 2 preparations in 3 hours after intravenous administration. Dexamethasone palmitate given as a lipid emulsion showed a much higher concentration in the blood, spleen, and inflamed tissues (carrageenan oedema), whereas dexamethasone sodium phosphate had a high concentration in the muscles. The anti-inflammatory activity of both preparations given intravenously was evaluated by using the preformed carrageenan granuloma pouch method. The anti-inflammatory activity of lipid emulsion dexamethasone was 5.6 times as potent as an equivalent amount of free dexamethasone. These results may indicate that corticosteroids which are incorporated in lipid emulsions are taken up by the reticuloendothelial system and some inflammatory cells much more than are free corticosteroids; thus they have a stronger anti-inflammatory activity. The clinical use of lipid emulsion corticosteroids for certain types of diseases is suggested.